CONTEMPORARY ISSUES REGARDING MEMBER STATE LIABILITY FOR INFRINGEMENTS OF EU LAW BY NATIONAL COURTS (EU and comparative law issues and challenges series (ECLIC), 2020)
The objective of the paper is the analysis of the development of the concept of liability of Member States of the European union for infringements of EU law committed by national courts of last instance. Focus is placed on the improvements in the Court of Justice of the European union’s (CJEU) case-law which have been made on the subject in the almost 25 years since its landmark judgment in the joined cases of Brasserie du Pecheur and Factortame, where it was firstly explicitly stated that a Member State may be held liable for damage arising even from decisions of the judiciary. Balancing on the thin line between the doctrine of judicial independence and the need for compensation of damages suffered by a judicial breach has always been an uncomfortable and arduous legal task, which is why the CJEU occasionally undertook to clarify and improve its position on the topic during the twenty first century. Even though serious advancement towards satisfying both of the aforementioned notions have been carried out by the CJEU in almost a quarter of a century since the Brasserie judgment, many legal predicaments and insufficiently answered questions which may arise in modern cases still remain present. The paper in its introductory part addresses the impact of the Francovich and Brasserie judgments which are considered landmark rulings in the area of Member State liability. In the central part, it demonstrates the more in-depth standpoint of the CJEU in the area of Member State liability for infringements committed within judicial decisions that firstly appeared in the CJEU’s Köbler judgment. Furthermore, it depicts how the CJEU further interpreted the criteria required for Member State liability for infringements of EU law by national courts to arise. The focal point of the paper deals with the most recent case-law of the CJEU that demonstrates how it attempts to tackle the issues around Member State liability in contemporary times. Since not everyone seems to be in full agreement with the current Member State liability arrangements in that regard, certain disagreements of legal scholarship with the CJEU’s latest solutions are also discussed. Finally, as a conclusion, a step-by-step demonstration of the obstacles which injured persons face in an action for damages suffered by a breach of EU law caused by a judicial decision of a national court of last instance is provided, and suggestions for future improvements and developments in this legal area are also pointed out.